2018
DOI: 10.1002/cssc.201801727
|View full text |Cite
|
Sign up to set email alerts
|

Compromising Between Phase Stability and Electrical Performance: SrVO3–SrTiO3 Solid Solutions as Solid Oxide Fuel Cell Anode Components

Abstract: The applicability of perovskite‐type SrVO3−δ in high‐temperature electrochemical energy conversion technology is hampered by the limited stability domain of the perovskite phase. The aim of the present work was to find a compromise between the phase stability and electrical performance by designing solid solutions in the SrVO3–SrTiO3 system. Increasing titanium content in SrV1−yTiyO3−δ (y=0–0.9) perovskites is demonstrated to result in a gradual shift of the upper‐p(O2) phase stability boundary toward oxidizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(29 citation statements)
references
References 78 publications
7
22
0
Order By: Relevance
“…XRD analysis confirmed that both as-synthesized STVN powders (1200 °C, 30 h) and sintered STVN ceramics (1450 °C, 10 h) comprised a Sr 1- a Ti 1- b V b O 3-δ solid solution with a cubic perovskite-type lattice (space group ) isostructural to the parent SrTiO 3 and SrVO 3 , and a fraction of metallic nickel phase. In agreement with the data on the Sr(Ti,V)O 3-δ system [ 34 , 48 ], the unit cell parameter of the perovskite phase shows a tendency to decrease with increasing vanadium content ( Table 1 ), which is consistent with the values of ionic radii for six-fold coordinated V 4+ and Ti 4+ (0.58 Å and 0.605 Å, respectively [ 49 ]). The only exception to this trend is S96V40N8, the sample with the highest nickel content.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…XRD analysis confirmed that both as-synthesized STVN powders (1200 °C, 30 h) and sintered STVN ceramics (1450 °C, 10 h) comprised a Sr 1- a Ti 1- b V b O 3-δ solid solution with a cubic perovskite-type lattice (space group ) isostructural to the parent SrTiO 3 and SrVO 3 , and a fraction of metallic nickel phase. In agreement with the data on the Sr(Ti,V)O 3-δ system [ 34 , 48 ], the unit cell parameter of the perovskite phase shows a tendency to decrease with increasing vanadium content ( Table 1 ), which is consistent with the values of ionic radii for six-fold coordinated V 4+ and Ti 4+ (0.58 Å and 0.605 Å, respectively [ 49 ]). The only exception to this trend is S96V40N8, the sample with the highest nickel content.…”
Section: Resultssupporting
confidence: 88%
“…The representative examples for the selected samples are depicted in Figure 4 . Similar to SrTi 1- y V y O 3-δ series [ 34 ] and other SrVO 3-δ -based materials [ 14 , 15 , 22 ], increasing deviation from the linear thermal expansion at higher temperatures can be partly attributed to a minor contribution of chemical expansion associated with the variable oxygen content in the perovskite lattice.…”
Section: Resultsmentioning
confidence: 82%
See 3 more Smart Citations